The Position of Legal Culture in the Legal System and Social Life - Setia Megawati Hutajulu; Agusmidah (CERED Indonesia Institute, 2025)
Indonesia is affirmed as a state of law as regulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, which contains the consequence that law must be the main foundation in the life of the nation and state. However, in practice, law enforcement still faces various problems, especially low public legal awareness and weak trust in law enforcement officials. This study aims to analyze the role of legal culture in realizing the effectiveness of the national legal system. The method used is normative legal research with a statutory and conceptual approach, descriptive-analytical in nature, and analyzed qualitatively. The results of the study indicate that the effectiveness of the law is not only determined by the substance and structure of the law, but is also greatly influenced by the legal culture of society which reflects values, attitudes, and views towards the law. Therefore, the development of legal culture and awareness through education, socialization, and legal counseling is a strategic step in realizing a democratic, just, and welfare-oriented state of law.